PENGEMBANGAN APLIKASI MANAJEMEN DATA BUKU MENGGUNAKAN APLIKASI VISUAL STUDIO CODE DENGAN FRAMEWORK LARAVEL - Adinda, Adinda Puteri Manisha; Efmi, Efmi Maiyana (METHODIKA: Jurnal Teknik Informatika dan Sistem Informasi, 2025)
The management of book data in libraries or bookstores often faces challenges in terms of efficiency and data accuracy. This research aims to develop a book management application using Visual Studio Code with the Laravel framework as an effective and user-friendly digital solution. The research method used is software development research with a prototyping approach. The results of the study indicate that this application simplifies book data management, including recording, editing, and deleting data with a user-friendly and responsive interface. In conclusion, the use of Laravel in the development of book management applications provides significant benefits in enhancing the productivity of book data management.